Pemberdayaan Ibu-Ibu Rumah Tangga Desa Sidoharjo untuk Meningkatkan Pendapatan Camilan Buah Mente Cryspi Aneka Rasa - Amron, Taufiq; Kharisma, Septian Dwita; Khotimah, Nurul; Sudarmiani, Sudarmiani (Keris: Journal of Community Engagement, 2025)
Sidoharjo Village has local potential in the form of abundant cashew fruit, but it is often wasted due to the lack of knowledge and skills of the community in processing it. This condition is both a problem and an opportunity for the economic empowerment of residents, especially housewives. This training activity aims to improve participants' skills and knowledge in processing cashew fruit into high-value snacks. The method applied involves hands-on practice and theory, including material selection, production techniques, and packaging. In addition, participants were also given training on marketing strategies, such as social media utilization and participation in local bazaars. The results of the training showed a significant improvement in participants' skills, with 70% of them successfully selling their products and recording an average income increase of 30-50%. The formation of joint business groups was done to ensure the sustainability of the program and encourage collaboration. The training not only had an impact on improving the family's economy, but also gave participants the motivation and confidence to be active entrepreneurs. Support from the government and local community is needed to expand the impact and ensure the sustainability of this local potential-based micro-enterprise. Overall, the program contributes to the optimization of local resources and strengthening the role of women in the community economy.